AB0698 A comparison of the effectiveness of mycophenolate mofetil or methotrexate in combination with prednisolone versus prednisolone alone in the treatment of large vessel vasculitis. (12th June 2018) - Smith, R.; Kilding, R.; Kuet, K.-P.; Akil, M.; Maxwell, J.
Abstract : Background: The mainstay of treatment for large vessel vasculitis is glucocorticoids. Immuno-suppressants, including mycophenolate mofetil (MMF) and methotrexate (MTX) are used as steroid-sparing agents. 1 A previous study at our centre showed MMF to have a steroid sparing effect in 97% of patients and to reduce C-reactive protein (CRP) in 80%. 2 Objectives: This study was undertaken to compare the efficacy of MMF or MTX combined with prednisolone or prednisolone alone in the treatment of large vessel vasculitis. Methods: Patients with large vessel vasculitis (LVV) confirmed on positron emission tomography (PET) scan and those meeting ACR criteria for a diagnosis of giant cell arteritis (GCA), treated with prednisolone alone, prednisolone with MMF or prednisolone with MTX started within 3 months of prednisolone being commenced and with a minimum follow up of 24 months were included in a retrospective single centre study. CRP and prednisolone doses were recorded at baseline, after 3, 6, 9, 12, 18 and 24 months of treatment and area under the curve (AOC) calculated for CRP and prednisolone doses. Median AOC prednisolone dose for patients treated with MMF or MTX was then compared with that of patients treated with prednisolone alone. A quantile regression model was also constructed to compare prednisolone dose between the 3 treatment groups, adjusted for CRP. StataCorp. 2013. Stata Statistical Software: Release 13 . College Station, TX: StataCorp LP was used for all statistical calculations. Results: 65 patients were included in the study, 41 with GCA and 24 LVV. 49 were female and 16 male. Mean age at diagnosis was 68; range 21 to 87. 37 patients were treated with prednisolone alone; 35 had GCA and 2 LVV. 20 were treated with MMF and prednisolone; 4 with GCA and 16 LVV. 8 were treated with MTX and prednisolone; 2 had GCA and 6 LVV. The AOC for prednisolone and CRP were not normally distributed across the cohort, and non-parametric methods were therefore used for comparisons. Median AOC prednisolone dose for the prednisolone only group was 68.0, (interquartile range (IQR) 17.7, n=37), for the MMF treated group 70.8 (IQR 28.7, n=20) and for the MTX treated group 67.8 (IQR 20.4 n=8). Median AOC CRP was highest in the group treated with prednisolone alone (58.9, IQR 34.5) compared to MMF (43.8, IQR 26.5) and MTX (49.3 IQR 67.5) but there were no statistical differences between median AOC prednisolone dose or CRP in either the unadjusted or regression models. Conclusions: No significant difference was shown between the groups. MMF is as effective as MTX and prednisolone alone in the treatment of LVV. However, there are limitations to the study. The patient group was small. There was no randomisation to treatment group; treatment choice was based on clinician preference. There was potential bias in that patients perceived to be more difficult to treat may have been given MMF or MTX in addition to prednisolone, and there was a higher proportion of patients with LVV compared to GCA in the MMF and MTX treated groups. References: [1] Mukhtyar C, et al. EULAR recommendations for the management of large vessel vasculitis. Ann Rheum Dis2009:68:318–23. [2] Smith R et al.Is Mycophenolate Mofetil Effective in the Treatment of Large Vessel Vasculitis? Rheumatology 54, Issue suppl_1, 1 April 2015, Pages i194. Disclosure of Interest: None declared